The Influence of Food Quality and Service Quality On Customer Satisfaction In Gofood Application Services In Padang City - Naseh Ulwan; Yulia Mandasari (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
This study aims to see the impact of Food and Service Quality on consumer satisfaction with Gofood application services in Padang. This type of research is quantitative descriptive with the Double Regression method. The population in this research is the population of the city Padang that has ever used Gofood applications. Sampling techniques are carried out using the purposeful method Sampling is carried out using the Limeshow formula this is because the total population is unknown the number of samples and is sampled by 97 samples, Data collection is carried out using a Likert scale that has tested its validity and reliability, Research results sho1) The food quality variable has a positive and significant effect on the consumer satisfaction variable with a sig0.011 value <0.05 and an r square value of 0.578 (57.8%) is obtained. The variation that occurs in high or low consumer satisfaction is due to variations in food quality and food quality. services while the rest (42.2%) is determined by other variables that have not been studied. 2) The service quality variable has a positive and significant effect on the sig value of 0.000<0.05, 3) The food quality and service quality variables simultaneously have a positive and significant effect on the consumer satisfaction variable with a sig value of 0.000